#TITLE_ALTERNATIVE# - ALFISYAH ARFIANTY (NIM : 10311009); Pembimbing : Dr. Aprilia, IRA
Bubble Nebula is an interstellar bubble which is located at the Perseus Arm of the Galaxy and cataloged as NGC 7635. BD +60o2522/SAO 20575 is known as the central star of Bubble Nebula, with mass of and still in main sequence stage. Bubble Nebula is the result of the interaction between the stellar wind of BD+60o2522 with an interstellar gas located around the star. An interstellar bubbles model can be used to estimate the formation of Bubble Nebula which defines the interaction between spherically symmetric stellar wind and an ambient interstellar gas creating an expanding spherical system, called bubble. The interaction structure of the stellar wind with the surrounding interstellar gas forming a bubble called a bubble dynamic structure. This structure is divided into 4 zones: stellar wind zone, shocked stellar wind zone, shocked interstellar gas zone, and ambient interstellar gas. On certain condition in the shocked stellar wind zone, the luminosity of this zone is larger than the mechanical luminosity of the wind. This makes the energy and the pressure of shocked stellar wind zone drop and collapse, causes the stellar wind collide directly with outer shell. The evolution of BD +60o2522 can be estimated by a web-based stellar evolution code, called as the EZ-Web. Based on this evolution code, the age of the system which needed for the interstellar bubbles model can be calculated. Based on the interstellar bubbles model, parameters such as radius, expansion velocity, temperature, and density of the Bubble Nebula can be determined. By comparing Bubble Nebula NGC 7635 with other bubble NGC 2359, we can estimate further evolution of Bubble Nebula, based on the evolution of the central stars.